Coastal blue space and depression in older adults. (November 2018) - Dempsey, Seraphim; Devine, Mel T.; Gillespie, Tom; Lyons, Seán; Nolan, Anne
Abstract: This paper tests whether higher exposure to coastal blue space is associated with lower risk of depression using data from The Irish Longitudinal Study on Ageing (TILDA), a nationally representative longitudinal study of people aged fifty and over in Ireland. We contribute to the literature on blue space and health by (i) using scores from the Center for Epidemiologic Studies Depression Scale (CES-D) to measure depression outcomes (ii) using new measures of coastal blue space visibility (iii) studying the association in an older population (iv) using data from Ireland. Our results indicate that exposure to coastal blue space is associated with beneficial mental health outcomes: TILDA respondents with the highest share of sea view visibility have lower depression (CES-D) scores, while distance from coastline is not statistically significant when views and proximity are both included in the model. This finding supports the idea that the primary channel through which coastal blue space operates to reduce depression scores is visual rather than related to physical proximity. Abstract : Highlights: We examine links between coastal blue space and depression in older age. Exposure to coastal blue space is associated with positive mental health effects. Individuals with the most sea view visibility have lower depression (CES-D) scores. Distance from coastline does not have a significant independent association.